Capsules and Nodes and Ruptures and Flows: Circulating Subjectivity in Neal Stephenson's "Snow Crash." - Swanstrom, Lisa (Science Fiction Studies, 2010)
Presents literary criticism of the book "Snow Crash" by Neal Stephenson. It discusses the ways that tensions between encapsulation and penetration in the network systems of "Snow Crash" contribute to a networked sense of self, especially in relation to the role of one of the book's characters, a hacker, who has access to the human mind. An overview of the story is also given.